Solve
"\\frac{dy}{dx}" =(x+2y-3)/(2x+y-3)
Our standard toolkit for DE's cannot be used. However, we can perform a transformation to remove the constants from the linear numerator and denominator.
Consider the simultaneous equations
"\\begin{cases}\n x+2y-3=0 \\\\\n 2x+y-3=0\n\\end{cases} \\implies \\begin{cases}\n x=1\\\\\n y=1\n\\end{cases}"
As a result we perform two linear transformations:
"\\begin{cases}\n u=x-1 \\\\\n v=y-1\n\\end{cases} \\implies \\begin{cases}\n x=u+1\\\\\n y=v+1\n\\end{cases} \\implies \\begin{cases}\n \\frac{dx}{du}=1\\\\\n \\frac{dy}{dv}=1\n\\end{cases}"
And if we substitute into the DE we get
"\\frac{dy}{dx}=\\frac{(u+1)+2(v+1)-3}{2(u+1)+2(v+1)-3}\\\\\n\n\\frac{dy}{dx}=\\frac{u+1+2v+2-3}{2u+2+v+1-3}\\\\\n\\frac{dy}{dx}=\\frac{u+2v}{2u+v}"
And utilising the chain rule we have
"\\frac{dy}{dx}= \\frac{dy}{dv}\\frac{dv}{du} \\frac{du}{dx} \\implies \\frac{dy}{dx}= \\frac{dv}{du}"
Thus we have a transformed equation
"\\frac{dv}{du}= \\frac{u+2v}{2u+v}\\\\"
This is now in a form that we can handle using a substitution of form v =wu, which if we differentiate wrt u using the product gives us.
Using this substitution into our modified DE, we get
"u \\frac{dw}{du}= \\frac{1+w^2}{2+w}\\\\"
This is now a separable DE, so we can rearrange and separate the variables to get:
"\\int \\frac{1}{u}du = \\int \\frac{2+w}{1+w^2}\\\\\n\\ln\n|\nw\n+\n1\n|\n\u2212\n\\ln\n|\nw\n\u2212\n1\n|\n\u2212\n1\n2\n\\ln\n\u2223\n\u2223\nw\n2\n\u2212\n1\n\u2223\n\u2223\n=\n\\ln\n|\nu\n|\n+\n\\ln\nC"
"\\frac{|\nw\n+\n1\n|}{\n|\nw\n\u2212\n1\n|\n\u221a\nw\n2\n\u2212\n1}\n=\n|\nC\nu\n|\\\\\n\\therefore (w+1)=Au^2(w-1)^3"
Then restoring the earlier w substitution, using "w\n\n=\n\n\\frac{v}{\n\n\n\nu}" we get:
"\u2234\nv\n+\nu\n=\nA\n(\nv\n\u2212\nu\n)^\n3"
"(\ny\n\u2212\n1\n)\n+\n(\nx\n\u2212\n1\n)\n=\nA\n(\n(\ny\n\u2212\n1\n)\n\u2212\n(\nx\n\u2212\n1\n)\n)^\n3"
"\u2234\ny\n+\nx\n\u2212\n2\n=\nA\n(\ny\n\u2212\nx\n)^\n3"
This is the General Solution, in implicit form.
Comments
Leave a comment